Masked phenomenon: renal and cardiovascular complications; review and updates - Elmukhtar Habas; Almehdi Errayes; Eshrak Habas; Gamal Alfitori; Ala Habas; Kalifa Farfar; Amnna Rayani; Aml Habas; Abdel-Nasser Elzouki (Blood Pressure)
Background In the in-clinic blood pressure (BP) recording setting, a sizable number of individuals with normal BP and approximately 30% of patients with chronic renal disease (CKD) exhibit elevated outpatient BP records. These individuals are known as masked hypertension (MHTN), and when they are on antihypertensive medications, but their BP is not controlled, they are called masked uncontrolled hypertension (MUHTN). The masked phenomenon (MP) (MHTN and MUHTN) increases susceptibility to end-organ damage (a two-fold greater risk for cardiovascular events and kidney dysfunction). The potential extension of the observed benefits of MP therapy, including a reduction in end-organ damage, remains questionable.Aim and methods This review aims to study the diagnostic methodology, epidemiology, pathophysiology, and significance of MP management in end-organs, especially the kidneys, cardiovascular system, and outcomes. To achieve the purposes of this non-systematic comprehensive review, PubMed, Google, and Google Scholar were searched using keywords, texts, and phrases such as masked phenomenon, CKD and HTN, HTN types, HTN definition, CKD progression, masked HTN, MHTN, masked uncontrolled HTN, CKD onset, and cardiovascular system and MHTN. We restricted the search process to the last ten years to search for the latest updates.Conclusion MHTN is a variant of HTN that can be missed if medical professionals are unaware of it. Early detection by ambulatory or home BP recording in susceptible individuals reduces end-organ damage and progresses to sustained HTN. Adherence to the available recommendations when dealing with masked phenomena is justifiable; however, further studies and recommendation updates are required.